A sustained-release PDGF-BB nanocomposite hydrogel for DM-associated bone regeneration. Issue 5 (3rd January 2023) - Li, Yaxin; Liu, Ziyang; Zhao, Chen; Xu, Chenci; Shin, Airi; Wu, Jiaqing; Li, Dejian; Lin, Kaili; Liu, Jiaqiang
Abstract : Schematic illustration of an injectable sustained-release PDGF-BB nanocomposite hydrogel promoting DM-associated bone regeneration and related mechanisms. Abstract : Regeneration of bone tissue in the environment of diabetes mellitus (DM) remains one of the clinical challenges, with malfunction of stem cells in a high-glucose microenvironment being the primary obstacle. We designed an injectable sustained-release PDGF-BB nanocomposite hydrogel. PDGF-BB, a star molecule for treating various complications of DM, was used for the first time for DM-associated bone regeneration, and we showed that it restored stem cell proliferation and migration and facilitated osteogenesis inhibition under high glucose stimulation by activating ERK and AKT pathways. To address the requirements for continuous PDGF-BB release in GelMA while also increasing mechanical strength, nanoclay LAPONITE® was added, which may still exhibit pro-osteogenic activity in diabetic environments by releasing bioactive ions (Si 4+, Mg 2+, and Li + ). This injectable hydrogel heals calvarial lesions successfully in diabetic rats and has the potential to be used as a direct and effective tool for treating diabetic patients.